ESL/EFL Learners' Responses to Teacher Written Feedback: Reviewing a Recent Decade of Empirical Studies - Yu, Rong; Yang, Luxin (Frontiers in Psychology, 2021)
Teacher written feedback (TWF) has long been regarded as a necessary pedagogical tool for improving the writing proficiency of ESL/EFL learners, while student responses to this feedback can often reflect its effectiveness. This paper reviews 64 articles appearing in high-ranking journals during 2010-2021 in terms of research methodology, theoretical framework and main findings. Analysis of these articles reveals few studies adopted any theoretical frameworks to examine learner responses to TWF and suggests a need for longitudinal naturalistic studies adopting mixed methods and some theoretical framework such as sociocultural theory of mind (SCT) to better explain learners’ dynamic engagement in response to TWF. The main findings of these previous studies reveal the diverse responses among learners at different language proficiency levels and in various sociocultural contexts. The results of the review indicate that future research could take classroom-based mixed-method research design to investigate learner variables.